Penerapan Strategi Bumper Sticker dalam Meningkatkan Hasil Belajar Siswa Materi Zakat Pada MAS Raudhatul Fata - Wahyuni, Sri; Zulkhairi, Zulkhairi (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This study aims to improve student learning outcomes on zakat material by using the Bumper Sticker strategy. This study used the method of classroom action research (PTK), which was carried out in two cycles, with the research subjects being class X students in a junior high school. Each cycle consists of planning, implementation, observation, and reflection. The results showed that the Bumper Sticker strategy was effective in improving student activeness, group collaboration, and individual learning outcomes. In cycle I, student activeness in group discussions reached 65%, which increased to 85% in cycle II. The average student score also increased from 75 in cycle I to 85 in cycle II, with the percentage of students who reached the Minimum Completion Criteria (KKM) increasing from 72% to 94%. The application of this strategy also shows that group discussions and the use of visual media (bumper stickers) can improve understanding of the concept of zakat. This study implies that the Bumper Sticker strategy can be used as an innovative learning alternative that increases students' active participation and understanding of the concepts of Fiqh material, especially zakat, and can be applied in the classroom for other topics that require conceptual understanding and collaboration.